1983
DOI: 10.1136/gut.24.9.818
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal absorption of amino acids and a dipeptide in pancreatic insufficiency.

Abstract: SUMMARY In this study a perfusion technique has been used to investigate in vivo jejunal absorption and transmural potential difference evoked by the neutral amino acids phenylalanine (56 or 20 mmol/l) and glycine (20 mmol/l), the dibasic amino acid lysine (56 or 5 mmol/l), and a dipeptide glycyl-l-phenylalanine (20 mmol/l) in 11 children with pancreatic insufficiency due to cystic fibrosis and in three children with other causes of exocrine pancreatic insufficiency. Net absorption and potential difference evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 17 publications
(6 reference statements)
1
14
0
2
Order By: Relevance
“…The breath test data in this study are in agreement with the generally accepted statement that intraluminal pancreatic digestion is very important in the overall process of protein assimilation 15. Other mechanisms possibly contributing to deficient protein assimilation in pancreatic disease, such as accelerated small intestinal transit or inadequate absorption,27 28 should be kept in mind as well.…”
Section: Discussionsupporting
confidence: 90%
“…The breath test data in this study are in agreement with the generally accepted statement that intraluminal pancreatic digestion is very important in the overall process of protein assimilation 15. Other mechanisms possibly contributing to deficient protein assimilation in pancreatic disease, such as accelerated small intestinal transit or inadequate absorption,27 28 should be kept in mind as well.…”
Section: Discussionsupporting
confidence: 90%
“…In both animal and human studies, elemental or semi-elemental small peptide formulas have been shown to be well tolerated and efficiently absorbed in a gut lumenal environment with little or no pancreatic enzyme secretion. [10][11][12][13] Case series have documented that TEN could be used safely as transitional feeding in patients who had peaked and had begun to resolve the inflammatory response associated with pancreatitis. 14-21…”
mentioning
confidence: 99%
“…Clinically overt vitamin B 12 deficiency, however, is rarely observed in C F patients (20). Reduced uptake of phenylalanine (16,21), cycloleucine (16) and glycine (21) but not of lysine (16) has been shown in C F patients. Finally, pronounced fecal bile acid loss has been documented in C F patients by Weber et al (22).…”
Section: Biochemical Findingsmentioning
confidence: 96%